PELANGGARAN PERSYARATAN TEKNIS DAN LAIK JALAN PENGGUNAAN “KNALPOT RACING” - Yuda Riyansah (JURNAL HUKUM DE'RECHTSSTAAT, 2016)
Bogor City Traffic Police have cracked down on the use of "racing exhaust" is the exhaust that create noise that should not be for the user "racing exhaust" that use will be dealt with by imposing a speeding ticket for anyone who is found to be using it. The using of "racing exhaust" the actual traffic police focus with a noisy exhaust, but for uniformity police finally cracked / menilang all types of non-standard exhaust. For the problem of "racing exhaust" did not meet the technical requirements specified Ministry of Transportation, car manufacturers as a product marketer must obtain permissions from the Ministry of Transportation regarding Technical Specifications and motor products to be marketed. Identify the problem in this research are: 1) What level of legal awareness violation technical requirements and road worthy in term of the use of "exhaust racing"? and 2) How to measure the traffic police in the discipline for violation of technical requirements and road worthy with the using of "racing exhaust" is associated with Law No. 22 of 2009 on Road Traffic and Road Transport ?. The purpose of the study are: 1) To determine, assess and analyze the level of legal awareness violation technical requirements and road worthy in terms the use of "exhaust system" and 2) To determine, assess and analyze the actions of the police traffic discipline for violation of technical requirements and acceptance way with the using of "racing exhaust" is associated with Law Number 22 Year 2009 regarding Traffic and Road Transportation. The method used is a normative juridical research method that is conceived as the norm of law, rules, principles or dogmas. The conclusion of this study is public awareness against the use of exhausting racing in the jurisdiction of Police Bogor City is still low and need to be enforced through the implementations of the traffic rules properly. Constraints are the limiting factor in the using of repression racing exhaust Bogor City Police jurisdiction is given the severity of the sanctions and the lack of awareness of traffic, but it is also caused by the presences of shops selling car accessories such tools freely. Factors that led to the use of racing exhaust that prestige factor, factor adolescent age, race factors, factors influence others. Efforts are being made the police to minimize the using of motor racing that preventive measures and repressive efforts. Efforts by the police in the jurisdiction of the police station in the city of Bogor minimize these violations carried out preventive and repressive that is by cracking down on traffic violators in juridical and non-juridical.